Ignite! Hot topics for the future of work: The future (age diverse) workforce - Petery, Gigi; Fisher, Gwenith (2020)
Seven scholars will discuss various ways in which an increasingly age diverse workforce reverberates across planning for and researching the future of work at an introductory to intermediate level. Presenters will summarize scientific research and offer practical solutions to stimulate and guide future research and practice. Audience questions and participation is encouraged.